A FIXED POINT THEOREM APPROACH TO GENERALIZED HALANAY INEQUALITIES - Anh Dung, Le (HNUE Journal of Science: Journal of Natural Sciences, 2025)
In this paper, we aim to reformulate a generalized Halanay inequality. A new approach using fixed point theorems for contraction mappings is presented. The obtained estimation can be utilized in various problems for nonlinear time-delay systems such as stability, dissipativity analysis and control design.